POSSIBLE NATURE OF THE RADIATION-INDUCED SIGNAL IN NAILS: HIGH-FIELD EPR, CONFIRMING CHEMICAL SYNTHESIS, AND QUANTUM CHEMICAL CALCULATIONS. Issue 1 (23rd December 2016) - Tipikin, Dmitriy S.; Swarts, Steven G.; Sidabras, Jason W.; Trompier, François; Swartz, Harold M.
Abstract: Exposure of finger- and toe-nails to ionizing radiation generates an Electron Paramagnetic Resonance (EPR) signal whose intensity is dose dependent and stable at room temperature for several days. The dependency of the radiation-induced signal (RIS) on the received dose may be used as the basis for retrospective dosimetry of an individual's fortuitous exposure to ionizing radiation. Two radiation-induced signals, a quasi-stable (RIS2) and stable signal (RIS5), have been identified in nails irradiated up to a dose of 50 Gy. Using X-band EPR, both RIS signals exhibit a singlet line shape with a line width around 1.0 mT and an apparent g -value of 2.0044. In this work, we seek information on the exact chemical nature of the radiation-induced free radicals underlying the signal. This knowledge may provide insights into the reason for the discrepancy in the stabilities of the two RIS signals and help develop strategies for stabilizing the radicals in nails or devising methods for restoring the radicals after decay. In this work an analysis of high field (94 GHz and 240 GHz) EPR spectra of the RIS using quantum chemical calculations, the oxidation–reduction properties and the pH dependence of the signal intensities are used to show that spectroscopic and chemical properties of the RIS are consistent with a semiquinone-type radical underlying the RIS. It has been suggested that semiquinone radicals formed on trace amounts of melanin in nails are the basis for the RIS signals. However, based on the quantum chemical calculations and chemical properties of the RIS, it is likely that the radicals underlying this signal are generated from the radiolysis of L-3, 4-dihydroxyphenylalanine (DOPA) amino acids in the keratin proteins. These DOPA amino acids are likely formed from the exogenous oxidation of tyrosine in keratin by the oxygen from the air prior to irradiation. We show that these DOPA amino acids can work as radical traps, capturing the highly reactive and unstable sulfur-based radicals and/or alkyl radicals generated during the radiation event and are converted to the more stable o-semiquinone anion-radicals. From this understanding of the oxidation–reduction properties of the RIS, it may be possible to regenerate the unstable RIS2 following its decay through treatment of nail clippings. However, the treatment used to recover the RIS2 also has the ability to recover an interfering, mechanically-induced signal (MIS) formed when the nail is clipped. Therefore, to use the recovered (regenerated) RIS2 to increase the detection limits and precision of the RIS measurements and, therefore, the dose estimates calculated from the RIS signal amplitudes, will require the application of methods to differentiate the RIS2 from the recovered MIS signal.